Robotic versus laparoscopic gastrectomy for gastric cancer: The largest meta-analysis. (October 2020) - Guerrini, Gian Piero; Esposito, Giuseppe; Magistri, Paolo; Serra, Valentina; Guidetti, Cristiano; Olivieri, Tiziana; Catellani, Barbara; Assirati, Giacomo; Ballarin, Roberto; Di Sandro, Stefano; Di Benedetto, Fabrizio
Abstract: Background: Minimally invasive surgery (MIS) has been increasingly used in the treatment of gastric cancer (GC). Laparoscopic gastrectomy (LG) has shown several advantages over open surgery in dealing with GC, although it is still considered a demanding procedure. Robotic gastrectomy (RG) is now being employed with increased frequency worldwide and has been reported to overcome some limitations of conventional LG. The aim of this updated meta-analysis is to compare surgical and oncological outcomes of RG versus LG for gastric cancer. Materials and methods: A systematic review and meta-analysis was conducted using the PubMed, MEDLINE and Cochrane library database of published studies comparing RG and LG up to March 2020. The evaluated end-points were intra-operative, post-operative and oncological outcomes. Dichotomous data were calculated by odds ratio (OR) and continuous data were calculated by mean difference (MD) with 95% confidence intervals (95% CI), and a random-effect model was always applied. Results: Forty retrospective studies describing 17, 712 patients met the inclusion criteria. With respect to surgical outcomes, robotic compared with laparoscopic gastrectomy was associated with higher operating time [MD 44.73, (95%CI 36.01, 53.45) p < 0.00001] and less intraoperative blood loss [MD -18.24, (95%CI -25.21, −11.26) p < 0.00001] and lower rate of surgical complication in terms of Dindo-Clavien ≥ 3 classification [OR 0.66, (95%CI 0.49, 0.88) p = 0.005]. With respect to oncological outcomes, the RG group showed a significantly increased mean number of retrieved lymph nodes [MD 1.84, (95%CI 0.84, 2.84) p = 0.0003], but mean proximal and distal resection margin distance and the recurrence rate were not significantly different between the two approaches. Conclusions: With respect to safety, technical feasibility and oncological adequacy, robotic and laparoscopic groups were comparable, although the robotic approach seems to achieve better short-term surgical outcomes. Moreover, a higher rate of retrieved lymph nodes was observed in the RG group. Highlights: Robotic Gastrectomy (RG) for Gastric Cancer is feasible and safe. The robotic approach seems to achieve better short-term surgical outcomes than laparoscopic gastrectomy. RG group showed a significantly greater mean number of lymph nodes retrieved than laparoscopic group.